A Comparative Study of the Skeletal Development of Epinephelus fuscoguttatus (♀) and E. tukula (♂) Hybrid Progeny and E. fuscoguttatus. (21st February 2023) - Wang, Xinyi; Tian, Yongsheng; Chen, Shuai; Li, Linlin; Duan, Pengfei; Li, Zhontong; Wang, Linna; Liu, Yang; Wang, Qingbin; Li, Wensheng; Zhao, Xia
Abstract : As a new breed of grouper hybrid breeding, EFT has the advantages of delicious flesh, fast growth, and high deformity rate. We explored the metamorphosis and skeletal development of Epinephelus fuscoguttatus and hybrids (EFT) of E. fuscoguttatus (♀) and E. tukula (♂). EFT grew slightly slower than E. fuscoguttatus during the larval period but grew faster during the juvenile period. The sequences of skeletal development were similar in EFT and E. fuscoguttatus . Newly hatched larvae did not have skeletons until 5 days after hatching (DAH) when head cartilage started to develop and complete at 43 days later. The vertebral column started to develop at 11 DAH and was completed at 38 DAH. Pectoral fin development began at 5 DAH and ossification was completed at 48 DAH in EFT and at 43 DAH in E. fuscoguttatus . Anal fin development started at 11 DAH and ossification was completed earlier in EFT than in E. fuscoguttatus . The caudal fins of the two groupers developed at 8 DAH and ossified earlier in EFT than in E. fuscoguttatus . In contrast, E. fuscoguttatus had one additional epural than EFT. These results provide important basic biological data for the growth and skeletal development of pure and hybrid grouper.